Distributed Storage Manager System for Synchronized and Scalable AV Services across Networks - Frank X. Sun; John Cosmas; Muhammad Ali Farmer; Abdul Waheed (International Journal of Digital Multimedia Broadcasting)
This paper provides an innovative solution, namely, the distributed storage manager that opens a new path for highly interactive and personalized services. The distributed storage manager provides an enhancement to the MHP storage management functionality acting as a value added middleware distributed across the network. The distributed storage manager system provides multiple protocol support for initializing and downloading both streamed and file-based content and provides optimum control mechanisms to organize the storing and retrieval of content that are remained accessible to other multiple heterogeneous devices.